Outcomes of Pediatric Fistulising Perianal Crohn’s Disease - Akkelle, Bilge S.; Sengul, Ozlem K.; Volkan, Burcu; Tutar, Engin; Ergelen, Rabia; Yardimci, Samet; Ertem, Deniz (Turkish Journal of Gastroenterology, 2021)
Background: Perianal disease is reported more widely in pediatric Crohn patients than in the past, and has been stated as an independent modifier of the disease behavior. In this study, we aimed to analyze the clinical characteristics and outcomes of fistulising perianal Crohn’s disease (fpCD) in the pediatric age group. Methods: A total number of 149 children with an established diagnosis of inflammatory bowel disease who have been diagnosed before 18 years of age and followed in our tertiary center were revised. Clinical, endoscopic, laboratory, and radiologic data of 50 patients with CD, who had at least 18 months follow-up data, were compiled. Results: Of 50 patients, 26 (52%) were diagnosed as fpCD (38% at onset). More than half of the patients without any notable external orifices around the perianal area were diagnosed as fpCD by an magnetic resonance imaging (MRI). Pediatric fpCD patients had a higher disease activity score and platelet count, lower serum albumin level, and a higher rate of granuloma in the biopsy samples, compared with non-fistulising patients. A considerably high rate of surgical interventions (i.e., seton placement 46% and abscess drainage 15%) was performed in combination with infliximab. Conclusion: Fistulising perianal Crohn’s disease seems to be more common than previously reported in the pediatric age group. A severe course of the disease might serve as a warning for the development of fpCD. A careful physical examination and use of perianal MRI with a high index of suspicion may increase the likelihood of fistula detection, hence may change the treatment strategy.